(untitled) (Altre Modernità, 2024)
The article addresses the aesthetic dimension of the ecosocial movement that between 2011 and 2014 opposed the project of exploitation of an open-pit gold mine undertaken by the Canadian company Edgewater and affecting the town of Corcoesto and other municipalities of both the Bergantiños region and the Costa da Morte of Galicia (Spain). By working within the interpretative frameworks of environmental humanities, environmental justice and social movements, the article analyzes the ways in which the uprising subjects undertook the process of framing the movement and the use of artistic language (especially literature, music, painting and performance) to convey the main strategies and actions of vindication and contention.